Trekking as a metaphor for medicine and medical education - Shankar, PR; Malhotra, V (Journal of College of Medical Sciences-Nepal, 2010)
Nepal is a favored trekking destination. Over the years a number of trekking styles have emerged and the author sees similarities between trekking styles and methods of medical education. Problem-based learning strategies make students more involved in their own learning and teachers act as facilitators. Trekkers and medical students mostly concentrate on the immediate trail or different subjects and are able to obtain an integrated and holistic view only occasionally. The nature of the doctor-patient relationship is changing with patients wanting to play a more active role in their treatment. Workers in the trekking industry and doctors slowly rise through the ranks. Often people take up jobs with more responsibilities and challenges which pay better. Technology has invaded both trekking and healthcare and most of the money is made by middlemen. In addition to other areas medicine is focusing on preparing patients for the final exist Key Words: Problem-based learning; doctor-patient relationship; medicine. DOI: 10.3126/jcmsn.v6i1.3607 Journal of College of Medical Sciences-Nepal, 2010, Vol. 6, No. 1, 67-69